Case report: Chronic inflammatory demyelinating polyneuropathy superimposed on Charcot–Marie-tooth type 1A disease after SARS-CoV-2 vaccination and COVID-19 infection - Li, Da; Yu, Hu; Zhou, Min; Fan, Weinv; Guan, Qiongfeng; Li, Li (Frontiers in Neurology, 2024)
Background There is growing evidence that severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) or COVID-19 infection is associated with the development of immune mediated neuropathies like chronic inflammatory demyelinating polyneuropathy (CIDP), but the impact of SARS-CoV-2 vaccination and COVID-19 infection on genetic disorders such as Charcot–MarieTooth (CMT) remains unclear. Case presentation A 42-year-old male with occulted CMT neuropathy type lA (CMT1A) who developed limb numbness and weakness after the second SARS-CoV-2-vaccination was confirmed by identifying characteristic repeats in the p11.2 region of chromosome 17. Due to the progressive deterioration of muscle strength over 8 weeks, limb atrophy, moderately elevated protein counts in the cerebrospinal fluid, and significant improvement with intravenous human immunoglobulin, which were characteristic of acquired inflammatory neuropathies, he was eventually diagnosed with CIDP superimposed on CMT1A. However, after a three-month plateau, the patient contracted COVID-19, which led to repeated and worsening symptoms of limb weakness and atrophy, thus was diagnosed with a recurrence of CIDP and treated with Intravenous immunoglobulin and methylprednisolone 500 mg/d for 5 consecutive days, followed by oral prednisone and mycophenolate mofetil tablets. On 2 month follow-up, he exhibited remarkable clinical improvement and could walk independently with rocking gait. After 1 year of follow-up, the patient’s condition was stable without further change. Conclusion Our case indicates that CMT1A can deteriorate after SARS-CoV-2 vaccination. Thus, SARS-CoV-2 vaccination should be considered a potential predisposing factor for CMT1A worsening. The possible superposition of CMTIA and CIDP in the context of SARS-CoV-2 infection or immunity suggests that any clinical exacerbation in patients with CMT1A should be carefully evaluated to rule out treatable superposition inflammation. In addition, electrophysiological and imaging examination of the proximal nerves, such as the axillary nerve, is helpful for the diagnosis of CIDP.